Fluorescence Quenching‐based Assay for Measuring Golgi endo‐α‐Mannosidase. Issue 11 (5th April 2019) - Sano, Kanae; Kuribara, Taiki; Ishii, Nozomi; Kuroiwa, Ayumi; Yoshihara, Toshitada; Tobita, Seiji; Totani, Kiichiro; Matsuo, Ichiro
Abstract: Golgi endo ‐α‐mannosidase (G‐EM) catalyzes an alternative deglucosylation process for N‐glycans and plays important roles in the post‐endoplasmic reticulum (ER) quality control pathway. To understand the post‐ER quality control mechanism, we synthesized a tetrasaccharide probe for the detection of the hydrolytic activity of G‐EM based on a fluorescence quenching assay. The probe was labeled with an N ‐methylanthraniloyl group as a reporter dye at the non‐reducing end and a 2, 4‐dinitrophenyl group as a quencher at the reducing end. This probe is hydrolyzed to disaccharide derivatives by G‐EM, resulting in increased fluorescence intensity. Thus, the fluorescence signal is directly proportional to the amount of disaccharide derivative present, allowing the G‐EM activity to be evaluated easily and quantitatively. Abstract : A novel tool for analysis of post‐ER quality control pathway : A FRET‐based probe for measuring the catalytic activity of Golgi endo ‐α‐mannosidase, a key player in post endoplasmic reticulum quality control, was synthesized. This is the first example of an assay method that enables the simple and quantitative detection of G‐EM in complex systems without the need for an added glucosidase inhibitor.